Thrombus entrapped by patent foramen ovale in a patient with pulmonary embolism: a case report - Sang Beom Nam; Chan Mi Kim; Sung-Ah Cho; Sungchan Chung; Yon Hee Shim (Korean Journal of Anesthesiology, 2015)
Thrombus-in-transit appears to increase the risk of mortality compared to pulmonary embolism alone and can require alteration in therapeutic plan. We present the case of a biatrial thromboembolus caught in transit across a patent foramen ovale diagnosed by intraoperative transesophageal echocardiogram in a 69-year-old female with acute pulmonary embolism and subsequent acute cerebral infarction. We suggest that echocardiography should be performed in a patient with suspected pulmonary thromboembolism to evaluate right heart function and diagnose emboli in transit.